Three new caespitose species of Senecio (Senecioneae, Compositae) from Central Andes - Calvo, Joel; Fuentes, Alfredo F. (Phytotaxa, 2018)
Three new species of Senecio belonging to the group of discoid caespitose species are described from the high Andes of Bolivia. One of them is also recorded from southern Peru. Special emphasis is placed on the color of the anthers, style-branches, and corollas, which are useful characters that were undervalued in previous taxonomic treatments dealing with this species assemblage. The three species are illustrated and pictures of living plants are included when available.